2021
DOI: 10.3389/fphar.2021.683575
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Anticancer Effects of JI017 on Two Prostate Cancer Cell Lines Involve Endoplasmic Reticulum Stress Mediated by Elevated Levels of Reactive Oxygen Species

Abstract: Prostate cancer is the second most commonly diagnosed cancer, and prostate cancer is the second most common cause of cancer death in United States men after lung cancer. Many therapies are used to treat prostate cancer, and chemotherapy is one of the most relevant treatments. However, chemotherapy has many side effects, and repeated administration of chemotherapeutic agents leads to acquired resistance. Thus, new drugs with few side effects are needed. We investigated the molecular mechanism of action of JI017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…As Zingiber officinale only constitutes a quarter of JI017, in this study, it might have been in insufficient quantity to be efficacious against both cold and mechanical allodynia. Furthermore, HPLC data identified decursin, nodakenin, aconitine, and 6-gingerol as major phytochemicals of JI017 [37]. Decursin is a major phytochemical of Angelica gigas, while aconitine is present in Aconitum carmichaelii.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As Zingiber officinale only constitutes a quarter of JI017, in this study, it might have been in insufficient quantity to be efficacious against both cold and mechanical allodynia. Furthermore, HPLC data identified decursin, nodakenin, aconitine, and 6-gingerol as major phytochemicals of JI017 [37]. Decursin is a major phytochemical of Angelica gigas, while aconitine is present in Aconitum carmichaelii.…”
Section: Discussionmentioning
confidence: 96%
“…JI017 consists of three medicinal herbs: Aconitum carmichaelii, Angelica gigas, and Zingiber officinale. In a previous study, JI017 showed anti-tumor potency in prostate cancer cell lines [37]. Although the analgesic efficacy of JI017 has never been reported, that of each of its components, in various pain models, has been documented [36,39,41].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…JI017 (an herb mixture composed of Aconitum carmichaelii, Angelica gigas and Zingiber officinale) exerts anticancer effect in prostate cancer cells via ROS-mediated ER stress. 123 Briefly, JI017 generates ROS and induces ER stress. Stress conditions induce the dissociation of GRP78/BIP (sensor key regulatory protein) from the IRE1α and PERK sensors, and subsequently activate sensor proteins, leading to eIF2α activation.…”
Section: Roles Of Er Stress At Mam In Cancermentioning
confidence: 99%